Human And Multi Freedom In The Quran - Zulkarnein Lubis; Robie Fanreza; Juli Maini Sitepu (Proceeding International Seminar of Islamic Studies, 2019)
Intelligence is not the same between one human and another human, but all humans must have intelligence, because intelligence is regulated by the human brain it self. With intelligence possessed by humans allows humans themselves to adapt to their daily lives. Intelligence is influenced by genetic factors, the environment, education, motivation and individual experience. Intelligence possessed by an individual will have an influence in his life making it easier for him to achieve something that is in accordance with their respective abilities. In the Koran intelligence is in the spiritual realm that is located in the heart. The concept of intelligence in the view of the Qur'an is studied in three concepts, including: The concept of Ulil Abshar, the concept of Ulin Nuha, and the concept of Ulil Albab. Whereas in a multi-intelligence view, intelligence is divided into many, among others: kinesthetic intelligence, linguistic intelligence, visual-spatial intelligence, mathematical logic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalistic intelligence, emotional intelligence and spiritual intelligence.